THE POWER OF SACRIFICE AS REFLECTED IN DAUGHTER FOR SALE BY SAMRUAM SINGH - Muhammad Arief Budiman (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2012)
Literature is one of the ways to understand the world and brings people to world of ideas and imaginations. The world that is believed could never happen in this world before. Sastrowardoyo says that novel does not give worth formula for intellect, but it suggests many possibilities on moral, social and psychology. Fiction stories encourage the ability to think, to dream, to bring our minds to all kinds of situation, and to create imaginative experiences. Besides, Tarigan says that in fiction stories there is a possibility of reality because one of many tasks of a writer is to create imaginative characters and to make them live in his stories. Life does not always run smoothly. Sometimes we face a condition that forces us to choose. Occasionally the choices we have do not suit our desire. We must sacrifice something to make our dream comes true. Sacrifice is needed to pursue our desires as in Samruam Singh’s Daughter for Sale. In Samruam Singh’s Daughter for Sale, the main character is Lung Maa. Lung Maa faces a very difficult situation. He needs money to pay the hospital where his wife is hospitalized. His garden does not produce much. His garden’s little production is only enough to pay his debt that already is mountainous. Thus Lung Maa chooses to sacrifice his daughter. Keywords: Daughter for sale, literature, power, sacrifice